(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
One series of N-phenyl pyrazoline analogues (K1-K5) were synthesized by reaction of substituted chalcones (C1-5) with phenyl hydrazine in acidic medium. The second series of 3, 4-dihydropyrimidine-2-one analogues (K6-K10) were synthesized by reaction of substituted chalcones (C1-5) with ethanolic urea in alkali medium. These substituted chalcones (C1-5) was prepared by reaction of acetophenone (a) and aromatic aldehydes (b1-5). The yield of the synthesized analogues ranged from 62-76%. The in-vitro anti-oxidant, anti-inflammatory and anti-tuberculosis screenings was performed. The result of all heterocyclic analogues (K1-K10) indicates that have significant in-vitro anti-oxidant, anti-inflammatory activity when compared to standard drugs. Among those analogues K1, K3, K6 & K8 were showed potent and analogues K2 & K7 were registered comparably good anti-oxidant and anti-inflammatory activities. The analogue K3 only exhibited potent activity against Mycobacterium tuberculosis. The analogues K1 and K6 exhibited moderate in-vitro anti-tuberculosis activity.